Las proyecciones en el teatro de Rodrigo García: la relación de subordinación entre el espacio fílmico y el espacio escénico - Bravo Tena, Eduardo Manuel (Talía. Revista de estudios teatrales, 2023)
Rodrigo García’s stage performances (1964), specifically those of the last two decades, are characterized by the presence of the resource of the screenings and, with them, the creation of filmic spaces in the stage space. He has included pre-recorded complete pieces, used the projection screen for the retransmission of scenes outside or inside the stage during the performance, shown the vision of the actors, shared texts... Screening time occupies a large part of the staging, with the stop of other actions to observe the images, with the projection above other scenic elements. About this aspect, the use of audiovisual in performances according to certain standards of multimedia dramaturgy comes into dispute, with the relationship of subordination between the filmic and stage spaces blurred, with the pertinent questioning of proper dramaturgical or theatrical use and of its possible cataloguing as another type of show with the combination of live arts and mediated arts.
Keywords: Postdramatic theatre; Scenic space; Filmic space; Projection; Tecnovivio